Left kickers choke during play-offs in soccer penalties - Schorer, J.; Rienhoff, R.; Loffing, F.; Baker, J. (Talent Development & Excellence, 2015)
Performances of elite athletes reflect the cognitive, psychological and physical potential of our species and inform our understanding of human performance. Studies have shown a strategic advantage for left-oriented performers in sport and other domains. In this study, we examined penalty-shooting performance of left- and right-footed soccer players during matches of normal (regular matches) and high (playoff matches) stress. In high stress situations, left-footed kickers in soccer `choke` more frequently than right-footed players, despite similar average performance in non-stressful situations. Although preliminary, these results suggest laterality-based differences in performance under stress.